Droplets of bosons at a narrow resonance - Wang, Ke; Preis, Thimo; Son, Dam Thanh (Physical review, 2025)
We consider bosons interacting through a narrow 𝑠-wave resonance. Such a resonance is characterized by an infinite scattering length and a large and negative effective range 𝑟0. We argue that any number 𝑁≥3 of bosons can form a self-bound cluster with the binding energy per particle increasing as 𝑁2 for 1≪𝑁≪(−𝑟0/𝑎bg)1/2, where 𝑎bg is the background scattering length (between atoms and molecules). In the opposite limit 𝑁≫(−𝑟0/𝑎bg)1/2, bosons form droplets with binding energy per particle saturating to a constant value independent of the particle number. The stability of clusters and droplets when the interaction is detuned from the resonance is also studied.
Gesehen am 26.11.2025